Reinventing the Business Model in the Tourism Industry based on Sustainable Circular Economy and Innovation - Daniela Avasiloaei (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2022)
Today, the whole globe is facing a series of crises unprecedented in modern histories, such as health, social, economic, environmental, etc. All these crises result from an unsustainable development model based on the misuse of the planet's natural resources, threats such as climate change, and conflicts with economic, social, and environmental impacts. The crisis caused by the pandemic has accentuated new patterns of behaviour and consumption, accelerated the technological revolution, and grown concerned for sustainability. Tourism is an industry that is particularly vulnerable to the effects of climate change, the consequences of which vary widely. Therefore, sustainable solutions are in the interest of the tourism sector, and the circular economy is a life-saving solution for the tourism industry. The transition from a linear to a circular economy is presented throughout the European Union as one of the major drivers of change and Innovation. This article aims to move towards a new business model in the tourism industry based on the circular economy and Innovation by setting out the principles for applying the circular economy in tourism. New business models can help us transform the tourism industry in this disruptive process.
Keywords: Q01; Z32; 330; Circular Economy; Innovation; Business Model; Tourism